MEDIATING ROLE OF TRUST BETWEEN EMOTIONAL INTELLIGENCE AND PROJECT TEAM PERFORMANCE IN TELECOMMUNICATION SECTOR - Umer Ishfaq; Asma Imran; Victoria Joseph; Dr Umbreen Haqdad; SamraAmeer; Dr. Muhammad Asif (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This study sought to examine the impact of emotional intelligence on project team performance by taking trust as mediator in telecommunication sector of Pakistan. The present study is based on the affective events theory (AET) that provide evidence that trust can be a mediator in this relation. Furthermore, this study focuses on mechanisms underlying in the association between performance and emotional intelligence at team and individual level. For accomplishment of study objective, data was collected from 105 employees of telecommunication sector, operating in Khyber Pakhtunkhwa. Pearson Product Moment Correlation analysis and regression analysis were used to analyze the data. The outcomes indicated that emotional intelligence positively associate with team performance, however trust was found as partially mediator. The present study is useful for the policy makers in telecom sector that how project team performance could be improved by deploying emotional intelligence.